To Know It Is to Loath It: Perceptions of Campaign Finance and Attitudes About Congress. Issue 5 (September 2019) - Donovan, Todd; Bowler, Shaun
We model attitudes about Congress as structured by perceptions of campaign finance. Attitudes about unlimited corporate and union spending are modeled as structured by knowledge about Congress. We find people with more factual knowledge of Congress were more likely to view unlimited independent corporate and union spending as having improper influence. We also found that people made some distinctions about sources of campaign finance. Knowledgeable people viewed unlimited independent expenditures as improper influence, but were less likely to perceive direct contributions from individuals to candidates as corrupt. When attitudes about Congress are estimated as a function of perceptions about financier influence, we find that perceptions about unlimited independent spending predicted negative views of representation and Congress, whereas perceptions of limited individual donations did not. People who knew the most about Congress were substantially more likely to find unlimited independent spending—the sort allowed by Citizens United —to be troubling.